2022
DOI: 10.1136/bmjopen-2021-057517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of influenza vaccination in long-term care homes: a cross-national retrospective observational study

Abstract: ObjectiveTo compare facility-level influenza vaccination rates in long-term care (LTC) homes from four countries and to identify factors associated with influenza vaccination among residents.Design and settingRetrospective cross-sectional study of individuals residing in LTC homes in New Brunswick (Canada), New Zealand, Switzerland, and the Netherlands between 2017 and 2020.ParticipantsLTC home residents assessed with interRAI assessment system instruments as part of routine practice in New Brunswick (n=7006) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…38 Twice as high VURs are reported in chronic obstructive pulmonary disease (COPD) patients, 39 and VUR in Swiss nursing homes was up to 63%. 40 At the international level, our findings are similar to VUR reported in Germany or Italy. [41][42][43]…”
Section: Vaccination Uptakesupporting
confidence: 87%
“…38 Twice as high VURs are reported in chronic obstructive pulmonary disease (COPD) patients, 39 and VUR in Swiss nursing homes was up to 63%. 40 At the international level, our findings are similar to VUR reported in Germany or Italy. [41][42][43]…”
Section: Vaccination Uptakesupporting
confidence: 87%
“…The use of the assessments enables quality monitoring and can inform decisions about eligibility criteria for access to services. This supports prioritisation of services based on identified needs, targeting priority groups or groups that are at higher relative risk of adverse outcomes [55][56][57][58][59][60][61].…”
mentioning
confidence: 61%
“…In 2021, home care data was linked to hospitalisation databases and population registries to explore the potential for illustrating care trajectories to inform policy [42]. Next, to raise awareness pertaining to data-driven quality issues and to illustrate the potential of structured clinical routine data, Switzerland participated in an international benchmark that was shared with clinical and political decision makers [43].…”
Section: Interrai Implementation In Switzerlandmentioning
confidence: 99%
“… 8 Several studies have confirmed that factors such as age, medical stability, health status, social interaction, cognitive decline, and smoking can influence elderly individuals’ decisions to receive influenza vaccination. 9 Additionally, factors such as education level, place of residence, confidence in vaccine safety, perception of disease risk, and awareness of the importance of influenza vaccination impact vaccine hesitancy in elderly individuals. 10 The benefits of seasonal influenza vaccination are short-term, as vaccine effectiveness is limited to the upcoming epidemic season, thus it is necessary to evaluate cost, vaccine safety, and effectiveness annually.…”
Section: Introductionmentioning
confidence: 99%